Advanced computational and design techniques in applied electromagnetic systems : proceedings of the International ISEM Symposium on Advanced Computational and Design Techniques in Applied Electromagnetic Systems, Seoul, Korea, 22-24 June, 1994 - Hahn, Song-yop (Elsevier studies in applied electromagnetics in materials, 1995)
This symposium was concerned with advanced computational and design techniques in applied electromagnetic systems including devices and materials. The scope of the proceedings cover a wide variety of topics in applied electromagnetic fields: optimal design techniques and applications, inverse problems, advanced numerical techniques, mechanism and dynamics of new actuators, physics and applications of magnetic levitation, electromagnetic propulsion and superconductivity, modeling and applications of magnetic fluid, plasma and arc discharge, high-frequency field computations, electronic device simulations and magnetic materials.